The researcher's guide to influencing policy - Reed, Mark S. (New York : Routledge, 2025)
"Designed to help researchers navigate the complex and ethical challenges of working with policy to effect change that is both deep and wide, this must-read book provides guidance on how to negotiate complex power dynamics, learn informing and influencing strategies and the different roles researchers can take within policy networks. Readers are invited to interrogate the assumption that evidence-based policy is either possible or desirable, question why they do the research they do and learn how they can use their power to give voice to those who are rarely heard. Based on two decades of Professor Reed's peer-reviewed work on research impact as well as his experience using his environmental research to influence policy around the world, this guide covers the crucial, tried and tested practical skills needed to communicate research effectively to policy audiences and collect evidence of policy impacts. Applicable to all disciplines and career stages, The Researcher's Guide to Influencing Policy provides the confidence needed to start engaging with policy safely, responsibly and effectively. It is time to get out of the echo chamber of research and policy elites and to start getting our hands dirty with the messy reality of real-world policy"--
Part 1: Responsible policy impact -- Policy as research impact -- A new approach to working with policy -- Working with complexity -- Navigating relationships -- Managing power dynamics -- Part 2: Strategic policy impact -- Is it appropriate to engage with policy yet? -- Strategic approaches to policy impact -- How to engage -- Part 3: Practical policy impact -- Policy briefs -- Policy infographics and presentations -- Other ways to influence policy -- Evaluating policy impacts -- Conclusion and further reading.
Keywords: Policy sciences; Research -- Political aspects; Evidence-based policy; Communication in education; Communication in politics; EDUCATION / Higher